The sensory system is a target for pharmaceutical therapy of overactive bladder - Christopher R. Chapple (Continence, 2024)
The concept that “the bladder is an unreliable witness” highlights the non-disease-specific nature of lower urinary tract symptoms (LUTS), which can arise regardless of anatomical differences between genders. This non-specificity has led to the broader classification of symptoms under LUTS, which include storage, voiding, and post-micturition symptoms. Overactive bladder (OAB) is characterised by urgency, often accompanied by frequency, nocturia, and, in some cases, incontinence. The symptoms of OAB do not always correlate with urodynamically proven idiopathic detrusor overactivity (IDO), indicating that afferent nerve activity plays a significant role. The complexity of bladder control involves a neural network spanning the brain, spinal cord, and peripheral ganglia. Current therapies, such as anticholinergics and beta-3 agonists, target both motor and sensory pathways, with emerging evidence suggesting that sensory modulation is crucial for effective treatment. Research using animal models has provided insights into the pharmacological mechanisms underlying bladder function, although these models have limitations in replicating human conditions. The importance of the sensory ‘web’ within the bladder’s mucosal and interstitial cell network is emphasised, as it significantly influences bladder compliance and sensory signalling. Recent advances, including the use of Onabotulinum toxin A and sacral neuromodulation, highlight the therapeutic potential of targeting sensory pathways in managing OAB symptoms.